An Evaluation of Dental Prosthetic Status and Prosthetic Needs Among Eunuchs (Trans Genders) Residing in Bhopal City, Madhya Pradesh, India: A Cross-Sectional Study - Hongal, S (Ann Med Health Sci Res, 2014)
BACKGROUND: Eunuchs are considered as the most vulnerable, frustrated, and insecure community. The accessibility to medical and dental facilities for the eunuchs is nearly nonexistent. Due to these reasons, they might be at a high risk of developing severe dental problems like tooth loss. AIM: The present cross-sectional study aimed to evaluate the dental prosthetic status and prosthetic needs among eunuchs residing in Bhopal city, Madhya Pradesh, India. SUBJECTS AND METHODS: On the basis of convenient nonprobability snowball sampling technique, all the self-identified eunuchs residing in the city of Bhopal along with a matched control consisting of cross section of the general population residing in the same locality was examined to evaluate the prosthetic status and prosthetic needs of the population. All the obtained data were entered into a personal computer on Microsoft excel sheet and analyzed using the software; Statistical Package for Social Science version 20. Data comparison was done by applying Chi-square test. RESULTS: A total of 639 subjects comprised of 207 eunuchs, 218 males and 214 females. Among all participants, 2.8% (18/639) were having prosthesis. The overall prosthetic status among males was 3.2% (7/218) followed by 2.9% (6/207) eunuchs and 2.3% (5/214) females. However, need for multi-unit and combination of one and more unit prosthesis for upper and lower jaws was higher in males compared to females and eunuchs, but the difference was not statistically significant. CONCLUSION: The findings of this study clearly demonstrate a high unmet need for prosthetic care among the population surveyed.